Parental Behaviors During Menstruation among female students (Pragyaratna प्रज्ञारत्न, 2024)
The study "Parental Behaviors during Menstruation among Female Students" embodies that good parental behavior involves talking openly about periods, giving girls the products they need, giving emotional support, and teaching them about staying clean and healthy during menstruation. How parents handle the stigma around periods also reflects their behavior. The purpose of the study is to examine the parental behaviors during the time of menstruation. Using quantitative and descriptive methods, the study selected 250 students by simple random sampling from the 650 enrolled on the two component sites. These campuses were chosen by convenience sampling from a pool of 22 in the Kathmandu Valley. Parents play a crucial role in providing emotional support, guidance, and education to their daughters about menstruation, empowering them to navigate this natural biological process with confidence and understanding. It examine that the diverse views on menstruation. While many respondent believed it as natural and don't limit activities, some follow traditional beliefs that restrict interactions with males and certain activities. Family practices also vary, from isolation to prioritizing hygiene. Such types of study can be done in affiliated campus and used qualitative research design.